Muslim Moderat, Wacana Politik, dan Pertarungan Relasi Kuasa: Moderate Muslims, Political Discourse, and the Struggle for Power Relations - Hafidz Hasyim (Fenomena, 2010)
This research focuses on: (1) the ideas produced by moderate Muslims in Jember in relation to the ongoing “democratic celebration”; (2) the ideological tendencies in the discourse of moderate Muslims; and (3) the “local tricks” employed to transform political discourse to build civil society. This field research analyzes data obtained from field findings, supported by references such as books, journals, and other supporting materials. The study is qualitative in nature. Its aim is to uncover the meaning constructed by moderate Muslims through interpretation, hermeneutics, and discourse analysis based on observation, interviews, documentation, and textual study. Penelitian ini memfokuskan pada: (1) gagasan‑gagasan yang dihasilkan oleh Muslim moderat di Jember sehubungan dengan “perayaan demokrasi” yang sedang berlangsung; (2) kecenderungan ideologis dalam wacana Muslim moderat; dan (3) “trik lokal” yang digunakan untuk mentransformasi wacana politik demi membangun masyarakat sipil. Penelitian lapangan ini mengolah data hasil temuan lapangan yang didukung oleh referensi berupa buku, jurnal, dan data pendukung lainnya. Penelitian ini bersifat kualitatif. Tujuannya adalah menemukan makna yang dibangun oleh Muslim moderat melalui interpretasi, hermeneutika, dan analisis wacana berdasarkan observasi, wawancara, dokumentasi, serta studi teks.